Alternative animal feeds from agroforestry plants - Salem, Abdelfattah Z.M.; Kunst, Carlos Roberto; Jose, Shibu (Springer, 2020)
This special issue idea originated when a few researchers from around the world came together with the goal of compiling the most up-to-date information on the use of alternative animal feed resources derived from agroforestry plants, including woody perennials. It is a common animal feeding practice in many parts of the world, particularly in the tropics; however, no comprehensive source of this information exists as attempted in this special issue. In addition to exploring alternative resources such as foliage of woody plants and other plant products and by-products for animal feed, papers included in this issue also addressed their impacts on ruminant and non-ruminant performance, health and welfare, and ruminal fermentation metabolism and mitigation of methane emission. We received 78 manuscripts from more than 21 countries and 45 papers were accepted following appropriate peer reviews. Overall, alternative feed resources, including woody plant foliage, improved animal performance, particularly during dry season. Several bioactive compounds were identified in agroforestry plants and they had positive impacts as antimicrobials against some the pathogenic bacteria and for controlling gastrointestinal parasites in livestock, which improved the health, welfare and production. Most alternative feeds added at low proportions with regular feed improved digestibility and decreased methane production.